Surface wave scattering by a material filled rectangular impedance groove in a reactive plane - Tayyar, Ismail Hakki (Elsevier Science Bv, 2011)
The problem of TE-polarized surface wave scattering from a rectangular impedance groove located on an infinite reactive plane which is filled with dielectric material is considered for a rather general case where the impedances of the horizontal and vertical sides of the groove have different values. The multiple interactions up to the second order between the edges of the groove are obtained to yield diffracted field. The diffraction problem is first reduced into a modified Wiener-Hopf equation and then solved approximately. The solution contains branch-cut integrals and two infinite sets of constants satisfying two infinite systems of linear algebraic equations. The approximate analytical evaluations of the corresponding integrals as well as the numerical solutions of the linear algebraic equation systems are obtained for various values of the parameters such as the surface reactance of the guiding plane, the vertical and horizontal wall impedances of the groove, the permittivity of the material loading, the width and the height of the groove which permit one to study the effect of these parameters on the diffraction phenomenon. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Surface-wave; Scattering; Wiener-Hopf; Impedance groove; Reactive plane